ANALYSIS OF FUTSAL PLAYER AND OFFICIAL UNDERSTANDING LEVEL TOWARDS FUTSAL LAWS OF THE GAME 2014/2015 - Hudayana, Herzi (Jurnal Kesehatan Olahraga, 2019)
Every game must have rules that govern the game, as well as futsal sports. First, every player or official team of futsal must understand the rules of futsal game. The lack of socialization about the rules of futsal game by District Futsal Association (AFKAB) makes the players and official team do not understand the rules of the game well. So the dispute between the referee with the players and team officers often happens and provoke the commotion. Therefore, we conduct research on the understanding of players and official team on the rules of futsal game. This study aims to determine the extent of players and team officers understand the rules of futsal game. This research is descriptive quantitative. The population of this study are all players and official team who qualify for the S4LCOM 2018 semifinal, which there are 40 players and 8 team members. Data collection techniques is using questionnaires. Team players and officials answered questions in the questionnaire in the appropriate answer column. The answers given should be honest and objective, in accordance with the actual situation. The data obtained were analyzed using quantitative descriptive statistics with persentasse. From 11 sub-indicators regarding the rules of futsal games, it can be seen how the level of understanding of players and team officials on the rules of futsal games. These results indicate the level of player's understanding of the rules of futsal games, namely 2 sub-indicators belonging to the category "Very Good", 3 sub-indicators belonging to the category "Good", 4 sub-indicators belonging to the category "Enough", and 2 sub-indicators belonging to the "Less" category. While the team officials showed that the level of understanding of the official team about the rules of futsal games are 7 sub-indicators belonging to the category "Very Good", 2 sub-indicators belonging to the category "Good", 1 sub-indicator belonging to the category "Enough", 1 the sub-indicator belongs to the "Less" category. From the results of this study concluded that players have a level of understanding with the category "Enough" which is indicated by a percentage of 36.3%. While officials team have a level of understanding with the category "Very Good" with a percentage of 63.6%. Keywords: understanding, game rules, futsal